Compulsive skin-picking behavior after deep brain stimulation in a patient with refractory obsessive–compulsive disorder: A case report. Issue 36 (September 2017) - Chang, Chun-Hung; Chen, Shin-Yuan; Tsai, Sheng-Tzung; Tsai, Hsin-Chi
Abstract: Rational: The therapeutic effect of deep brain stimulation (DBS) for refractory obsessive–compulsive disorder (OCD) has been studied, but complications after this treatment have rarely been noted. Patient Concerns: A 28-year-old man with treatment-resistant OCD received bilateral ventral capsule/ventral striatum stimulation for 12 months. Diagnosis: Compulsive skin-picking behavior and infection were noted following 12-month DBS treatment. Intervention: We removed the implanted right-side pulse generator. Outcomes: The local inflammation and skin-picking behavior gradually improved. The stimulator device was re-implanted 4 months later. Lessons: We suggest that patients with the OC spectrum should be evaluated for skin-picking behaviors during presurgical and postsurgical follow-up to reduce the infection and device removal rates.